PROSES PERENGKAHAN ASAM OLEAT BASIS MINYAK SAWIT MENJADI FRAKSI GASOLINE - SYAHRIR, IRMAWATI (Jurnal Teknik Kimia, 2009)
Many kinds of new energy resources which are renewable and dependable come from various kinds of vegetable oil, thus it can substitute petroleum oil which people usually use.Oil palm oil is quite advantageous to be used as an alternative energy resources in Indonesia, since Indonesia is the world’s second largest producer of oil palm oil. Fuel made from oil palm oil has been researched and is more friendly to environment, because it has less polution potential when used, since it’s free from sulphur andnitrogen. Oil palm oil has long hydrocarbon chain which makes it possible to be used as vegetable fuel.The aim of this research is : to learn the influence of temperature and flow velocity of N2 gas on catalytic splitting of oil palm oil-based oleat acid into kerosene fraction.Spliting process of oil palm oil-based oleat acid is done in steady woodpile micro reactor at varioustemperatures and flow velocities of feed at 1 atm pressure. The result of the splitting process is analyzed with FID chromatography gas with Q poraplot column type, for liquid phase product. Research is done by heating  oleat acid in feed tank until 360°C temperature and reactor at 370-500°C temperature, and N2 gas is flowed into tank as carrier gas with 90-180 ml/minute flow velocity. Oleat acid steam and N2  gas flow into steady woodpilereactor which is coated with heater element and is filled with 0.6 gram catalyst. Spitting reaction is done for 75minutes. Bound time limit for kerosene fraction as shown by chromatogram is 12.6-17.5 minutes, anaylisis result for commercial kerosene for 450°C temperature and flow velocity of N2 gas 155.28 ml/minutes from fractionarea percentage chromatogram, kerosene fraction is 27.2645%.  Keywords: palm oil, kerosene fraction, fixed reactor.